The association between socioeconomic status and health-related quality of life among young and middle-aged maintenance hemodialysis patients: multiple mediation modeling - Mai, Qingxin; Xu, Siyi; Hu, Jingyi; Sun, Xiaoming; Chen, Gangyi; Ma, Zhen; Song, Yang; Wang, Chao (Frontiers in Psychiatry, 2023)
Objective: To explore the relationship between socioeconomic status (SES), illness perception, social functioning, and health-related quality of life (HRQoL) of young and middle-aged maintenance haemodialysis (MHD) patients and the internal mechanism of action.Design: A multicenter cross-sectional study.Methods: An aggregate of 332 young and middle-aged MHD patients were enrolled from haemodialysis centres in four general hospitals in Guangzhou, Guangdong, China, from June to December 2022. The questionnaires used included one for general demographic data, the Brief Illness Perception Questionnaire (BIPQ), Social Dysfunction Screening Scale (SDSS), and the 12item Short Form Health Survey (SF-12).Results: Both SES and HRQoL were negatively correlated with illness perception and social functioning, respectively. SES was positively correlated with HRQoL. Illness perception was positively correlated with social functioning. The indirect effects of illness perception and social functioning on the relationship between SES and HRQoL were 0.33 and 0.31, making up 41.06% and 38.91% of the sum. The chain indirect effect of illness perception and social functioning was 0.10, making up 12.59% of the total effect, while gender did not play a moderating role.Conclusions: Illness perception and social functioning may independently and accumulatively mediate the association between SES and HRQoL. Nurses should consider developing individual This is a provisional file, not the final typeset article intervention programmes for young and middle-aged MHD patients with low SES, focusing on establishing targeted counselling and health education strategies corresponding to illness perception and social functioning to help patients improve their HRQoL.